83.7k views
0 votes
Help me please. I need it

Help me please. I need it-example-1
User JyoonPro
by
5.3k points

1 Answer

4 votes

Answer/Step-by-step explanation:

Use the distance formula,
d = √((x_2 - x_1)^2 + (y_2 - y_1)^2), to solve each problem.

1. Distance between A(0, 0) and B(-5, 7):


(0, 0) = (x_1, y_1)


(-5, 7) = (x_2, y_2)


AB = √((-5 - 0)^2 + (7 - 0)^2) = √((-5)^2 + (7)^2) = √(25 + 49)


AB = √(74)

2. Distance between A(-3, 1) and B(-11, 1):


(-3, 1) = (x_1, y_1)


(-11, 1) = (x_2, y_2)


AB = √((-11 - (-3))^2 + (1 - 1)^2) = √((-8)^2 + (0)^2) = √(64 + 0)


AB = √(64) = 8

3. Distance between A(-3, -2) and B(5, 6):


(-3, -2) = (x_1, y_1)


(5, 6) = (x_2, y_2)


AB = √((5 - (-3))^2 + (6 - (-2))^2) = √((8)^2 + (8)^2) = √(64 + 64)


AB = √(128) = √(64*2)


AB = 8√(2)

4. Distance between A(-2, -5) and B(-6, 1):


(-2, -5) = (x_1, y_1)


(-6, 1) = (x_2, y_2)


AB = √((-6 - (-2))^2 + (1 - (-5))^2) = √((-4)^2 + (6)^2) = √(16 + 36)


AB = √(52)

None of the choices are correct

User Damini Suthar
by
6.2k points